The effect of Persea americana Mill. seed extract on inflammatory cells and fibroblast formation in tooth extraction socket healing - Yessy Ariesanti; Irvan Septrian Syah Putra Rasad; Maylan Nimas; Nadira Syabilla (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Inflammatory cells and fibroblasts have an essential role in the wound healing process. Persea americana Mill. seed categorises as a waste; it contains rich nutrients that can accelerate wound healing activity. Purpose: This study aims to determine the effect of Persea americana Mill. seed against inflammatory cells and fibroblast formation in tooth extraction socket healing. Methods: Ninety-six Sprague Dawley rats had their lower left molars removed. Forty-eight rats tested for inflammatory cells were divided into four groups: negative control group (IC1), positive control group (IC2), Persea americana Mill. seed extract concentrations of 50% (IE1) and 90% (IE2). Another 48 rats used for fibroblast were divided into three groups: the control group (FC1), Persea americana Mill. seed concentrations of 50% (FE1) and 90% (FE2). The gel was applied to the socket under general anaesthesia. Four rats from each group were decapitated for histopathological tissue preparations with Haematoxylin Eosin (HE) staining on the 3rd, 5th and 7th days for inflammatory cells and the 3rd, 5th, 7th and 14th days for fibroblast formation. The preparations for each research were scored under the microscope at 40x magnification. The obtained data was analysed using the Kruska—Wallis and the Mann—Whitney test. Results: A significant decrease (p<0.05) of inflammatory cells in IE2 on the 5th and 7th day. A significant increase (p<0.05) of fibroblast formation between treatment and control groups and no significant difference (p>0.05) between FE1 and FE2 was based on the interval days. Conclusion: Persea americana Mill. seed extract can decrease the inflammatory cells and accelerate the fibroblast formation in tooth extraction socket healing.